Indigenous cultures and employee efficiency: the moderating effect of cronyism in state-owned enterprises in Ghana - Fred Awaah; Morounkeji Olanrewaju (Public Administration and Policy, 2023)
Purpose – This paper examines the relationship between indigenous cultures and employee efficiency and how cronyism strengthens or weakens the relationship in the Ghanaian state-owned enterprises (SOEs) in response to the employee efficiency. Design/methodology/approach – This study employs a quantitative approach by a cross-sectional survey to collect data from 400 workers in ten SOEs in Ghana. The analysis is done by using descriptive statistics and hierarchical regression techniques. Findings – The findings indicate that showing gratitude is the predominant indigenous culture in the SOEs of Ghana while irregularity (absenteeism) is not dominant. Moreover, the practice of cronyism is high. It reveals that the indigenous cultures, except for respect for the elderly, relate negatively to employee efficiency, and cronyism strengthens the relationship between indigenous cultures and employee efficiency. Originality/value – The paper contributes to the literature by providing empirical evidence that cronyism effectively strengthens the relationship between indigenous cultures and employee efficiency in a developing country. Strategies to discourage cronyism should be the key focus of public administrators, as well as mechanisms to limit the practice of adverse indigenous cultures.